Kratom and Pain Tolerance: A Randomized, Placebo-Controlled, Double-Blind Study - Vicknasingam, Balasingam; Chooi, Weng Tink; Rahim, Azlan Abdul; Ramachandram, Dinesh; Singh, Darshan; Ramanathan, Surash; Yusof, Nur Sabrina Mohd; Zainal, Hadzliana; Murugaiyah, Vikneswaran; Gueorguieva, Ralitza; Mansor, Sharif Mahsufi; Chawarski, Marek C (The Yale journal of biology & medicine, 2020)
: Kratom has a long history of traditional medicine use in Southeast Asia. Consumption of kratom products has also been reported in the US and other regions of the world. Pain relief is among many self-reported kratom effects but have not been evaluated in controlled human subject research. : Kratom effects on pain tolerance were assessed in a randomized, placebo-controlled, double-blind study. During a 1-day inpatient stay, participants received a randomized sequence of kratom and placebo decoctions matched for taste and appearance. Pain tolerance was measured objectively in a cold pressor task (CPT) as time (seconds) between the pain onset and the hand withdrawal from the ice bath. Health status, vital signs, objective, and subjective indicators of withdrawal symptoms, self-reported data on lifetime kratom use patterns, and assessments of blinding procedures were also evaluated. : Twenty-six males with the mean (SD) age 24.3 (3.4) years were enrolled. They reported the mean (SD) 6.1 (3.2) years of daily kratom consumption. Pain tolerance increased significantly 1 hour after kratom ingestion from the mean (SD) 11.2 (6.7) seconds immediately before to 24.9 (39.4) seconds 1 hour after kratom consumption (F(2,53.7)=4.33, p=0.02). Pain tolerance was unchanged after consuming placebo drinks: 15.0 (19.0) seconds immediately before and 12.0 (8.1) seconds 1 hour after consumption of placebo (F(2,52.8)=0.93, p=0.40). No discomfort or signs of withdrawal were reported or observed during 10-20 hours of kratom discontinuation. : Kratom decoction demonstrated a substantial and statistically significant increase in pain tolerance. Further rigorous research on kratom pain-relieving properties and a safety profile is needed.